Measuring the socioeconomic impact of last-mile infrastructure development in Latin America and the Caribbean - Pau Puig Gabarró; Raúl L. Katz; Hernan Galperin; Fernando Callorda; Enrique Iglesias Rodríguez; Antonio García Zaballos; Marcos Robles; Ramiro Valencia (Inter-American Development Bank (IDB), 2022)
The objective of this study is to estimate the socioeconomic impact of the deployment of last-mile digital infrastructure in Latin America and the Caribbean. To measure the impact of the economic and social aspects of this type of infrastructure, the analysis differentiates according to the geographic context (urban and rural), gender, and educational level, and details the effects and channels that link the deployment of last-mile infrastructure with socioeconomic benefits. The results of this study show that broadband improves job creation, the passage to formality, and salaries for the entire population. The findings indicate that the difference between the higher-skilled and lower-skilled segments of the population is considered in terms of the level of impact. The results also reveal that broadband deployment can generate an increase in inequality between genders, between the urban and the rural population, and between individuals with more years of formal education and individuals with fewer years of formal education if it is not accompanied by public policies that allow access equal use of this technology. This evidence confirms findings in previous studies that highlight the complementarity between broadband and skill levels in estimating benefits. For this reason, the contribution of public policies should be considered as a compensatory mechanism to counteract unintended effects. The set of results constitutes a rich base of empirical information that could help the governments of the region to make policy decisions, taking into account the importance of extending last-mile deployment to the rural context.
Keywords: G18; G28; L96; L86; L42; 330; digital infrastructure; connectivity; inclusion; digital economy